Uterine Inflammatory Myofibroblastic Neoplasms With Aggressive Behavior, Including an Epithelioid Inflammatory Myofibroblastic Sarcoma: A Clinicopathologic Study of 9 Cases. (January 2022) - Collins, Katrina; Ramalingam, Preetha; Euscher, Elizabeth D.; Reques Llanos, Armando; García, Angel; Malpica, Anais
Abstract : The experience with uterine inflammatory myofibroblastic neoplasms with an unfavorable outcome is limited. We present the clinicopathologic features of 9 such cases, including 8 inflammatory myofibroblastic tumors (IMTs) and 1 epithelioid inflammatory myofibroblastic sarcoma (EIMS). Median patient age for the IMT group was 50.5 years; the patient with EIMS was 43 years old. Patients presented with abnormal uterine bleeding, presumed fibroids, pelvic pain, arthralgia and low-grade fever, as well as an incidental finding. Median tumor size for the IMTs was 8.5 cm. The borders were either infiltrative or well-circumscribed. Histologically, IMTs were purely fascicular or myxoid or showed predominance of one or the other pattern. Seven tumors were spindled, and 1 was both spindled and epithelioid. Tumors had variable nuclear atypia, ranging from grade 1 to 3. All tumors had an inflammatory infiltrate-predominantly lymphocytic, majority had necrosis (62.5%) and none had lymphovascular invasion. 7/8 (87.5%) tumors were positive for ALK-1 by immunohistochemistry (IHC). One tumor was negative for ALK-1 by IHC but was positive for ALK fusion by fluorescence in situ hybridization and had TNS1-ALK fusion by next-generation sequencing (NGS). Three other tumors with NGS testing showed one of the following ALK -fusion partners: FN1, DCTN1, and IGFBP5. The EIMS had infiltrative borders, myxoid and hyalinized patterns, epithelioid cells, and no lymphovascular invasion. This tumor was ALK-1 positive by IHC, had ALK rearrangement by fluorescence in situ hybridization and RANBP2-ALK fusion by NGS. Extrauterine disease at time of diagnosis was noted in 2/8 (25%) of IMTs, and in the single case of EIMS. Seven patients had surgery as primary treatment, 1 patient had neoadjuvant chemotherapy and 1 patient declined treatment. Patients with recurrence were treated with a combination of chemotherapy, targeted therapy, radiotherapy or hormonal therapy. Most patients (71.4%) recurred within 24 months (mos). Two thirds of patients were alive with disease at last follow up (mean 43.6 mos). The patient with EIMS was alive with disease at 22 mos. IMT referral cases were initially diagnosed as smooth muscle tumors in 87.5% of cases; while the EIMS was diagnosed as high-grade endometrial stromal sarcoma. Lack of consideration of IMT in the differential diagnosis of smooth muscle tumors with myxoid features can result in misdiagnosis and under-utilization of targeted therapy in these patients.